The genus Macroocula Panfilov in Egypt, with two new species (Hymenoptera: Bradynobaenidae: Apterogyninae) - Gadallah, Neveen S.; Soliman, Ahmed M.; Al-Shahat, Ahmed M.; Hossni, Mohammed T. (Zootaxa, 2015)
The genus Macroocula Panfilov in Egypt is reviewed. Seven species were previously recorded from Egypt: M. magna (Invrea, 1965), M. mahunkai Argaman, 1994, M. morawitzi (Radoszkowski, 1888), M. nigriventris (Invrea, 1960), M. nitida (Bischoff, 1920), M. savignyi (Klug, 1829) and M. sinaica (Invrea, 1963). Macroocula brothersi Gadallah & Soliman, sp. nov. (Egypt, Wadi Shab, Red Sea) and M. salehi Gadallah & Soliman, sp. nov. (Egypt, Wadi Shaghab, Aswan) are described and illustrated. The subspecies M. nitida nitida (Bischoff, 1920) and M. nitida patrizii (Invrea, 1932) are raised to species level. An illustrated key and a faunistic list of Macroocula species are given.